Pengaruh Model Pembelajaran Role Playing Berbasis Tri Hita Karana Terhadap Kompetensi Pengetahuan IPS Siswa Kelas IV SD Gugus Untung Surapati - I Gede Widnyana (Jurnal Ilmiah Sekolah Dasar, 2018)
This research aims to determine the significant differences in the competence of IPS group knowledge of students who are taught by role playing learning model based on Tri Hita Karana. This research type is quasi experiment research with nonequivalent control group design. Samples were taken by random sampling technique. The sample in this research is the fourth grade students of SDN 6 Sumerta amounting to 39 students as the group which is recommended with the role playing model based on Tri Hita Karana and the fourth grade students of SDN 11 Sumerta are 38 students as control group with conventional learning. The data collection is done by using the test method in the form of the usual double choice objective test with four answers. The data obtained were analyzed using t-test analysis. The result of data analysis is tvalue = 8,315> ttable = 2,000 for 5% significance and dk = 75. Based on test criteria, H0 is rejected. The average score of IPS knowledge competence in the group that was studied with the role playing model based on Tri Hita Karana was X = 84,31, while in the group recommended with conventional learning was X = 69,11. Based on the result of this research, it can be concluded that there is influence of role playing model based on Tri Hita Karana on the competence of IPS knowledge of fourth grade students of SD Untung Surapati Unit, Denpasara Timur Sub District, Lesson Year 2016/2017. concluded that the model of learning group investigastionÂ  affect learning outcomes Civics class VI students ofÂ  SD N 2 Datah regency of Karangasem.